PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI KELURAHAN SEMBILAN SEPULUH ULU KOTA PALEMBANG - Desi Desi; Irwan Septayuda (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to analyze the influence of service quality provided by governmental institutions, particularly the Sembilan Sepuluh Ulu Subdistrict Office in Palembang City, on public satisfaction through indicators of Tangibles, Reliability, Responsiveness, Assurance, and Empathy, utilizing the Structural Equation Modeling (SEM) PLS 3 method. The results indicate that Tangibles and Assurance positively influence Public Satisfaction, whereas Reliability and Responsiveness do not show a positive influence. Empathy is also proven to have a positive influence on Public Satisfaction. The managerial implications suggest that the Subdistrict Office can enhance public satisfaction by addressing and improving aspects that have been shown to have a positive influence. The theoretical implications of this research contribute to understanding the relationship between service quality and public satisfaction, particularly in the context of governmental institutions. For future researchers, it is recommended to conduct a deeper analysis regarding the implementation of solutions, particularly by considering the effectiveness of training, the application of service information systems, and continuous evaluation of the transparency and efficiency of services.